Real‐world genomic landscape of colon and rectal cancer - Markus Schulze; XiaoZhe Wang; Jawad Hamad; Julia C. F. Quintanilha; Lincoln W. Pasquina; Julia F. Hopkins; Juergen Scheuenpflug; Zheng Feng (FEBS Open Bio)
MAPK signaling activation is an important driver event in colorectal cancer (CRC) tumorigenesis that informs therapy selection, but detection by liquid biopsy can be challenging. We analyze real‐world comprehensive genomic profiling (CGP) data to explore the landscape of alterations in BRAF or RAS in CRC patients (N = 51 982) and co‐occurrence with other biomarkers. A pathogenic RAS or BRAF alteration was found in 63.2% and 57.9% of colon and rectal cancer samples, respectively. In a subset of 140 patients with both tissue‐ and liquid‐based CGP, the sensitivity of liquid for results found by tissue was 100% when ctDNA tumor fraction was at least 1%, illustrating the utility of tissue and liquid biopsy in detecting driver alterations in CRC.